Peningkatan Persepsi Ibu Hamil tentang Pentingnya Layanan Pemeriksaan Triple Eliminasi (HIV, Sifilis dan Hepatitis B) melalui Kegiatan Pendidikan Kesehatan di Posyandu Bhayangkara - Fatiah, Mona Safitri; Purba, Rispah; Tompul, Renti B R (Warta LPM, 2024)
The vertical transmission of Human Immunodeficiency Virus (HIV), Syphilis and Hepatitis B (triple elimination) from pregnant women to the fetus is very alarming, with the proportion of pregnant women who know the status of the three diseases during pregnancy in Posyandu Bhayangkari still below 3%, lower than the set target (75%). The purpose of this activity is to increase the level of knowledge, attitudes and perceptions of pregnant women regarding the importance of triple elimination services through counseling activities. The method used was Community Based Survey (CBR) conducted for one day on May 24, 2024 in Posyandu Bhayangkari. The target of the activity is pregnant women who perform pregnancy checks at Bhayangkari Posyandu, Buper, Waena, Jayapura City, both those who perform pure first visit (K1) and K1 access, a total of 30 people. There are three stages in this activity, namely: question and answer method (conducted with Posyandu officers to ensure the accuracy of the targets used), community education method (providing counseling), and question and answer method (filling out questionnaires before and after counseling). The results demonstrated a statistically significant increase in knowledge (21.2 points), attitude (45.4 points), and perception (42.8 points) about the triple elimination examination following the administration of counseling. The findings indicate that counseling is an effective strategy for enhancing the knowledge, attitudes, and perceptions of pregnant women regarding triple elimination checks. This activity proposes the implementation of regular counseling sessions for pregnant women during Posyandu activities and the enhancement of health workers' capacity to provide effective counseling and counseling related to triple elimination checks. This will ensure that informants are adequately informed about the purpose and benefits of triple elimination checks during pregnancy, which are aimed at preventing the transmission of HIV, syphilis, and hepatitis B from mother to fetus.